The Effect of Work Motivation, Career Development, Compensation System, Employee Engagement and Job Satisfaction on Employee Performance in XYZ State-Owned Enterprise in Gorontalo - Datau, Rahmawatie (Lentera Ilmu Nusantara, 2025)
BUMN XYZ is a BUMN that works in the field of electricity. As an electricity provider in Indonesia, which provides the best electricity services to the public, BUMN XYZ has an extensive business network throughout Indonesia, one of its business units is BUMN XYZ in Gorontalo which is located in Gorontalo Province. Key Performance Indicator (KPI) serves to define and measure organizational goals, which are fundamental elements for any sustainable organization and the success of any company. In a company like BUMN XYZ Gorontalo, it is important to improve Employee Performance in employees with the aim that company performance can increase. The purpose of this study was to determine the effect of Work Motivation, Career Development, Compensation System, Employee Engagement and Job Satisfaction on Employee Performance. To obtain quantitative data through questionnaires distributed online, a crosssectional method was used. The questionnaire has been modified based on questions found in previous literature. All demographic data was obtained from 160 employees of BUMN XYZ Gorontalo, who have worked for at least one year. The data obtained will be analyzed using SmartPLS software. The results of the study indicate that there is a positive relationship between Transformational Leadership, Motivation, Career Development, Work Environment and Job Satisfaction on Employee Performance. But Transformational Leadership and Work Environment do not show a significant relationship either directly with Job Satisfaction or the relationship with Employee Performance even though it has been mediated by Job Satisfaction. This research produces managerial implications that can help BUMN XYZ Gorontalo in improving Employee Performance in order to achieve company goals, namely the best performance. This research has a number of limitations, which are followed by suggestions for future research.